2011
DOI: 10.1080/13691058.2010.521576
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive medicalisation, fear of infertility and teenage pregnancy in Brazil

Abstract: In Brazil, as in many other countries, teenage pregnancy is widely recognised as a public health problem. Buttressed by a public health science of the economics of teenage pregnancy that emphasises the postponement of parenthood as key to poverty reduction, young people's lack of appreciation for medical knowledge of contraceptives is most often credited for failed attempts to reduce teenage pregnancy. Based on a longitudinal ethnographic study conducted in Pelotas, Brazil, with young people over the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Adolescent mothers in both studies reported a distrust in contraception because they had witnessed adolescent women falling pregnant regardless of contraception. The overwhelming fear of weight gain while using contraception was echoed by our participants and also by Brazilian women in a study conducted by Goncalves et al [53] The participants in our study also noted the negative attitudes of their partners towards condoms, which compromises safe sex. The disfavour of South African men towards condoms are noted by Mash et al [54] Likewise, Kanda and Mash [55] found that Batswana men and women in their study believed that condoms reduces pleasure, and interferes with a sustained erection.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Adolescent mothers in both studies reported a distrust in contraception because they had witnessed adolescent women falling pregnant regardless of contraception. The overwhelming fear of weight gain while using contraception was echoed by our participants and also by Brazilian women in a study conducted by Goncalves et al [53] The participants in our study also noted the negative attitudes of their partners towards condoms, which compromises safe sex. The disfavour of South African men towards condoms are noted by Mash et al [54] Likewise, Kanda and Mash [55] found that Batswana men and women in their study believed that condoms reduces pleasure, and interferes with a sustained erection.…”
Section: Discussionsupporting
confidence: 58%
“…Myths about contraception also influence sexual health practices [17,53], as the beliefs that the participants held about contraception shaped their health practices and their sexual risk taking behaviours. This finding concurs with a study by Ngum Chi Watts et al [17] that was conducted among Australian adolescent mothers who also believed the myth that contraception causes sterility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effort to prevent teenage girls from becoming pregnant and proceeding to raise their children is the hallmark of public health and social policies across a wide range of Western nations (Arai, 2003;Daguerre and Nativel, 2006;Hoggart, 2012;Luker, 1996, 94). This concerted policy effort now has a global reach (Gonçalves et al, 2010;Mkhwanazi, 2010;WHO, 2011). At least in part, this is fuelled by Western global health and development stakeholders such the WHO and the Bill and Melinda Gates foundation (Koffman and Gill, 2013).…”
Section: Adolescent Motherhood: a Global Developmental Hazard?mentioning
confidence: 98%
“…Estudos realizados na área da sexualidade e do gênero apontam o quão difícil tem sido a gestão da sexualidade e da contracepção no par heterossexual, as difi culdades de uso regular de métodos anticoncepcionais, com ocorrência de gravidez imprevista e aborto em condições inseguras 2 para a saúde das mulheres (Bajos et al, 2002(Bajos et al, , 2003Cabral, 2012;Gonçalves et al, 2011;Luker, 1975;Spencer et al, 2014;Teixeira el al., 2012). As difi culdades de negociação entre os casais sobre o uso do preservativo masculino e/ou de outro método de proteção à gravidez, devido à forte hierarquia de gênero e uma cultura sexual que preconiza a "naturalidade" e a espontaneidade do ato sexual, impedem o planejamento prévio dos encontros sexuais, admitindo-se um certo grau de incerteza e do risco de se engravidar (Bozon;Heilborn, 2006;Cabral, 2011).…”
Section: Contexto Da Contracepção De Emergência No Brasilunclassified